2023
DOI: 10.1093/eurheartjsupp/suac123
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 and COVID vaccination on cardiovascular outcomes

Abstract: COVID-19 is an independent risk factor for cardiovascular disease. COVID-19 vaccination may prevent this, but in some cases, COVID-19 vaccination may cause myocarditis or pericarditis. Patients with COVID-19 may present with non-specific symptoms that have a cardiac origin. This review examines the cardiovascular complications of COVID-19 infection and the impact of COVID-19 vaccination. COVID-19 cardiovascular complications include myocardial injury, pericarditis, coagulopathy, myocardial infarction, heart fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…17 Symptoms that are both cardiac and GIT-related account for less than 20% of symptoms, with rare events being severe. 25,28 The health status of severe cases needs to be investigated to identify the cause of severe reactions.…”
Section: Discussionmentioning
confidence: 99%
“…17 Symptoms that are both cardiac and GIT-related account for less than 20% of symptoms, with rare events being severe. 25,28 The health status of severe cases needs to be investigated to identify the cause of severe reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Post-vaccination, acute MI rates were significantly lower than those associated with COVID-19 infection in other countries [ 72 ]. Some studies exhibit conflicting outcomes, with some suggesting that COVID-19 vaccination might decrease the risk of cardiovascular events like myocarditis and MI, while others indicate an increased risk [ 73 ]. Further investigation into the relationship between COVID-19 vaccinations and MI, considering various demographic and health-related factors, is essential to comprehensively understand the potential risks and benefits associated with vaccination.…”
Section: Reviewmentioning
confidence: 99%
“…A recent review in 2023 found COVID-19 vaccine to be beneficial in reducing deleterious impact of COVID-19 in patients with HF 55 . It is important to note that drawing conclusions regarding the efficacy of the COVID-19 vaccine in patients with HF is premature at this stage, primarily due to the lack of RCTs.…”
Section: Role Of Covid-19 Vaccinesmentioning
confidence: 99%